The Influence of Digital Marketing and E-WOM Promotion on Repurchase Intention with Trust In Store as Intervening Variables - Nidya Rizkawati; Adil Abdillah (Journal of Social Science and Humanities, 2025)
The research aims to identify and analyze the effect of digital marketing and e-wom promotion on repurchase intention with trust in store as an intervening variable. The type of research used in this research is quantitative research. The sample in this study was 50 respondent. Methods of data collection in this study using a questionnaire and literature study. The data analysis method used in this research is the instrument test, the classical assumption test, the multiple linear regression analysis test t test and the hypothesis test. Based on the research results obtained multiple linear equations Y1 = 0.156 X1 + 0.118 X2 + 0.388 X3 + 0.740. The effect of the E-Wom Promotion variable on repurchase intention through trust in store obtains a value of 0.171. The digital marketing path coefficient value for direct consumer trust in stores is 0.156 and a significance at 0.002, which means that the hypothesis can be accepted because the path coefficient value is positive (0.156) and the significance value is less than 0.05 (0.002 <0.05). This means that there is a direct positive influence from E-Wom Promotion on trust in store at Hasanah Boutique Mojokerto.